Hard Coat Film
A hard coat film with a sesamol-type benzotriazole ultraviolet absorber in a UV-curable resin layer addresses the issues of light-induced deterioration and brightness maintenance in organic EL displays, achieving desired transmittance levels and thickness for modern displays.
Patent Information
- Application Number
- JP2024008034
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-01-23
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-09-27
AI Technical Summary
Existing hard coat films for organic electroluminescent (EL) displays fail to adequately reduce light transmittance at critical wavelengths (365 nm and 405 nm) to prevent polymer deterioration and dye fading, while maintaining display brightness and durability, and are not thin enough to meet modern display thickness requirements.
A hard coat film with a laminated ultraviolet curable resin layer containing a sesamol-type benzotriazole ultraviolet absorber of specific molecular weight (15,000 to 35,000) is applied, achieving less than 1% transmittance at 365 nm, less than 10% at 405 nm, and 81% at 436 nm, with a thickness between 2.0 μm and 6.0 μm, enhancing durability and maintaining display quality.
The film effectively protects organic EL displays from deterioration and maintains brightness by reducing light transmittance at harmful wavelengths, while being thin enough to fit modern display designs, and retains performance after a light resistance test.
Smart Images

Figure 0007618371000001 
Figure 0007618371000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a hard coat film used for optical members, and more particularly to a hard coat film that can be used as a protective film for panel displays such as organic electroluminescence (EL) displays, liquid crystal displays (LCDs), and plasma displays, and display device parts such as touch panels. [Background technology]
[0002] For example, the display surface of displays such as organic electroluminescence (EL) displays and liquid crystal displays (LCDs) is required to be scratch-resistant so that the display surface is not scratched during handling and visibility is not reduced. For this reason, a hard coat film having a hard coat layer provided on a substrate film is generally used to impart scratch resistance to the display surface of the display.
[0003] In recent years, as displays have become thinner and lighter, the components thereof have also become thinner. For example, there is a demand for thinner hard coat films used in polarizing plates of displays. Furthermore, when the above-mentioned hard coat film is used as a protective film for the surface of an organic EL display, for example, the hard coat film is required to satisfy a number of requirements, such as not adversely affecting the color and brightness of the display of the organic EL display, being able to improve the durability (light resistance) of the light-emitting element of the organic EL display, and being able to suppress deterioration of the display of the organic EL display.
[0004] As a conventional technique, for example, Patent Document 1 discloses a film-forming composition containing a triazine ring-containing polymer capable of forming a thin film having a high refractive index and excellent light resistance. Also, for example, Patent Document 2 discloses a film-forming composition containing a triazine ring-containing hyperbranched polymer capable of forming a film having high transparency and high light resistance and having a thickness of 1000 nm or more. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2017 / 110810 [Patent Document 2] International Publication No. 2013 / 094664 Summary of the Invention [Problem to be solved by the invention]
[0006] In order to suppress damage such as deterioration of some polymers used in organic EL displays and fading and discoloration of dyes, it is required to sufficiently reduce the light transmittance at wavelengths such as 365 nm and 405 nm. Furthermore, in order to improve the durability (light resistance) of light-emitting elements in recent organic EL displays, it is required to sufficiently reduce the light transmittance at, for example, 405 nm in order to protect the light-emitting elements. However, the films obtained from the film-forming compositions disclosed in the above Patent Documents 1 and 2 have very high light transmittance at, for example, 365 nm and 405 nm, and cannot solve problems such as suppressing damage such as deterioration of some polymers used in the above organic EL displays and fading and discoloration of dyes, and improving the durability (light resistance) of the light-emitting elements of organic EL displays.
[0007] Furthermore, although various hard coat films of the prior art other than those disclosed in Patent Documents 1 and 2 are known, it has been difficult to obtain a hard coat film that can simultaneously satisfy requirements such as not adversely affecting the color and brightness of the display of the organic EL display, improving the durability (light resistance) of the light-emitting element of the organic EL display, and suppressing deterioration of the display of the organic EL display.
[0008] Therefore, the object of the present invention is, first, to provide a hard coat film which, when used as a protective film for the surface of an organic EL display, does not adversely affect the color or brightness of the display of the organic EL display, can improve the durability (light resistance) of the light-emitting element of the organic EL display, and can suppress deterioration of the display of the organic EL display; second, to provide a hard coat film which can maintain the above-mentioned performance even after a light resistance test is performed on the hard coat film; and third, to provide a hard coat film which can be made thinner. [Means for solving the problem]
[0009] As a result of intensive research into solving the above problems, the present inventors have found that the above problems can be solved by the invention having the following configuration. That is, the present invention has the following configuration.
[0010] (First invention) The hard coat film is characterized in that a hard coat layer made of an ultraviolet curable resin containing a sesamol-type benzotriazole ultraviolet absorber having a weight average molecular weight in the range of 15,000 to 35,000 is laminated on at least one surface of a transparent substrate, and the hard coat film has a light transmittance at a wavelength of 365 nm of less than 1%, a light transmittance at a wavelength of 405 nm of less than 10%, and a light transmittance at a wavelength of 436 nm of 81% or more.
[0011] (Second Invention) The hard coat film according to the first aspect of the present invention is characterized in that, after the hard coat film is subjected to an accelerated light resistance test in accordance with JIS-K-5600-7-7 for 100 hours, the light transmittance at a wavelength of 365 nm is less than 1%, the light transmittance at a wavelength of 405 nm is less than 10%, and the light transmittance at a wavelength of 436 nm is 81% or more.
[0012] (Third Invention) The hard coat film according to the first or second aspect of the present invention is characterized in that the thickness of the hard coat layer is more than 2.0 μm and less than 6.0 μm.
[0013] (Fourth Invention) The hard coat film according to any one of the first to third inventions is characterized in that the amount of the sesamol-type benzotriazole ultraviolet absorber is 20 to 60 parts by mass per 100 parts by mass of the ultraviolet curable resin of the hard coat layer.
[0014] (Fifth Invention) The hard coat film according to any one of the first to fourth aspects of the present invention is characterized in that the transparent substrate is a triacetyl cellulose film, a polyethylene terephthalate film, or a cycloolefin polymer film. Effect of the Invention
[0015] According to the present invention, it is possible to provide a hard coat film that, when used as a protective film for the surface of an organic EL display, can improve the durability (light resistance) of the light-emitting element of the organic EL display without adversely affecting the color and brightness of the display of the organic EL display, and can suppress deterioration of the display of the organic EL display. Furthermore, according to the present invention, it is possible to provide a hard coat film that can maintain the above-mentioned performance even after the hard coat film is subjected to a light resistance test. Furthermore, according to the present invention, it is possible to provide a hard coat film that allows for a thinner film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, the embodiment for carrying out the present invention will be described in detail, however, the present invention is not limited to the following embodiment. In this specification, "XX to △△" means "greater than or equal to XX and less than or equal to △△" unless otherwise specified.
[0017] As described in the first aspect of the present invention, the hard coat film of the present invention is characterized in that a hard coat layer made of an ultraviolet curable resin containing a sesamol-type benzotriazole ultraviolet absorber having a weight average molecular weight in the range of 15,000 to 35,000 is laminated on at least one side of a transparent substrate, and the hard coat film has a light transmittance at a wavelength of 365 nm of less than 1%, a light transmittance at a wavelength of 405 nm of less than 10%, and a light transmittance at a wavelength of 436 nm of 81% or more. The configuration of the hard coat film of the present invention will be described in detail below.
[0018] [Transparent base material] First, the transparent substrate of the hard coat film will be described. As the substrate to be coated with the hard coat film of the present invention, a transparent film substrate is usually used. The transparent film substrate used in the present invention is not particularly limited as long as it has transparency, and examples thereof include resin films made of acrylic resins, triacetyl cellulose, polyethylene terephthalate, cycloolefin polymers, polycarbonate, polyethylene naphthalate, polyethylene, polytrimethylene terephthalate, polypropylene, polybutylene terephthalate, polybutylene naphthalate, polystyrene, polymethyl methacrylate, polystyrene glycidyl methacrylate, aromatic polyimides, alicyclic polyimides, polyamideimides, and mixtures thereof. Here, "transparency" refers to a total light transmittance of 80% or more, measured in accordance with JIS-K7136.
[0019] In the present invention, from the viewpoints of transparency, optical properties, and versatility in the optical film for displays, among these film substrates, triacetyl cellulose film, polyethylene terephthalate film, cycloolefin polymer film, and the like are particularly suitable.
[0020] In the present invention, the thickness of the transparent substrate is appropriately selected depending on the application, but from the viewpoint of the demand for thinner hard coat films in accordance with the thinning and weight reduction of displays, it is preferably 50 μm or less, particularly preferably 30 μm or less, while from the viewpoint of mechanical strength, handleability, etc., it is preferably 10 μm or more.
[0021] [Hard coat layer] Next, the hard coat layer of the hard coat film will be described. In the present invention, the hard coat layer contains at least an ultraviolet curable resin and a sesamol-type benzotriazole ultraviolet absorber having a weight average molecular weight in the range of 15,000 to 35,000. In the present invention, it is preferable to use an ultraviolet-curable resin as the resin contained in the hard coat layer, since it imparts surface hardness (pencil hardness, scratch resistance) to the hard coat layer, and it is possible to adjust the degree of crosslinking by the amount of exposure to ultraviolet light, thereby enabling adjustment of the surface hardness of the hard coat layer.
[0022] The ultraviolet curable resin used in the present invention is not particularly limited as long as it is a transparent resin that is cured by irradiation with ultraviolet (UV), but it is preferable that the resin is made of a UV-curable polyfunctional acrylate having three or more (meth)acryloyloxy groups in one molecule in order to obtain coating hardness and form a three-dimensional crosslinked structure of the hard coat layer. Specific examples of UV-curable polyfunctional acrylate having three or more (meth)acryloyloxy groups in one molecule include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane ethoxy triacrylate, glycerin propoxy triacrylate, and ditrimethylolpropane tetraacrylate. The polyfunctional acrylate may be used not only alone but also in combination of two or more kinds.
[0023] Furthermore, the ultraviolet-curable resin used in the hard coat layer is preferably a monomer, oligomer, or polymer having a weight-average molecular weight in the range of 500 to 3600, more preferably 500 to 3000, and even more preferably 500 to 2400. If the weight-average molecular weight is less than 500, the curing shrinkage upon curing by UV irradiation is large, and the phenomenon (curl) in which the hard coat film warps toward the hard coat layer side is large, causing problems in the subsequent processing steps and poor processing suitability. If the weight-average molecular weight exceeds 3600, the flexibility of the hard coat layer is increased, but the hardness is insufficient, which is not suitable. The weight average molecular weight in the present invention is an average molecular weight obtained by gel permeation chromatography (GPC) analysis in terms of standard polystyrene.
[0024] Furthermore, when the weight average molecular weight of the ultraviolet curable resin used in the hard coat layer is less than 1500, the number of functional groups in one molecule is preferably 3 or more and less than 10. When the weight average molecular weight of the ultraviolet curable resin is 1500 or more, the number of functional groups in one molecule is preferably 3 or more and less than 20. Within the above range, curling can be suppressed and appropriate processing suitability can be maintained.
[0025] In addition to the above-mentioned ultraviolet-curable resin, the resin contained in the hard coat layer may be a thermoplastic resin such as polyethylene, polypropylene, polystyrene, polycarbonate, polyester, acrylic, styrene-acrylic, or cellulose, or a thermosetting resin such as a phenol resin, urea resin, unsaturated polyester, epoxy, or silicone resin, within a range that does not impair the hardness and scratch resistance of the hard coat layer.
[0026] In the present invention, the hard coat layer contains, in addition to the ultraviolet-curable resin, a sesamol-type benzotriazole ultraviolet absorber having a weight-average molecular weight in the range of 15,000 to 35,000 (hereinafter, sometimes referred to as "the ultraviolet absorber of the present invention" in this specification).
[0027] The ultraviolet absorbent of the present invention is prepared by reacting a sesamol-type benzotriazole monomer with, for example, an acrylate resin component to polymerize it.
[0028] Here, the sesamol-type benzotriazole monomer is, for example, represented by the following general formula (I), and is a derivative of a compound in which sesamol is bonded to the nitrogen atom at the 2-position of the benzotriazole ring.
[0029] [ka]
[0030] In the above formula, R1 represents a hydrogen atom or a methyl group, and R2 represents a linear or branched alkylene group having 1 to 6 carbon atoms, or a linear or branched oxyalkylene group having 1 to 6 carbon atoms. Specific examples of the sesamol-type benzotriazole monomer represented by the above general formula (I) include 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]ethyl methacrylate, 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]ethyl acrylate, 3-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]propyl methacrylate, 3-[2-(6 -Hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]propyl acrylate, 4-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]butyl methacrylate, 4-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]butyl acrylate, 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yloxy]ethyl methacrylate acrylate, 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yloxy]ethyl acrylate, 2-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propanoyloxy]ethyl methacrylate, 2-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propanoyloxy]ethyl acrylate, 4-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propanoyloxy]ethyl acrylate 4-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propanoyloxy]butyl acrylate, 2-(methacryloyloxy)ethyl-2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-carboxylate, 2-(acryloyloxy)ethyl-2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, 4-(methacryloyloxy)butyl-2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, 4-(acryloyloxy)butyl-2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, and the like.
[0031] The ultraviolet absorber of the present invention can be obtained by polymerizing the above-mentioned sesamol-type benzotriazole monomer with other monomer components (e.g., acrylate resin components such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, octyl (meth)acrylate, and nonyl (meth)acrylate). The polymerization method can be a conventionally known solution polymerization method, emulsion polymerization method, suspension polymerization method, bulk polymerization method, and the like.
[0032] In the present invention, it is important to use a sesamol-type benzotriazole ultraviolet absorber having a weight-average molecular weight in the range of 15,000 to 35,000. In contrast, when a sesamol-type benzotriazole-based ultraviolet absorber having a weight-average molecular weight of less than 15,000 is used, the light transmittance at 405 nm cannot be sufficiently reduced, as shown in the comparative example described later, and this causes a problem of degradation of the display of the organic EL display. Also, when a sesamol-type benzotriazole-based ultraviolet absorber having a weight-average molecular weight of more than 35,000 is used, the performance cannot be maintained even after a light resistance test at a wavelength of 405 nm, and this causes a problem of degradation of the display of the organic EL display, and a problem of failure to achieve improvement in the durability (light resistance) of the light-emitting element. The weight average molecular weight of the sesamol-type benzotriazole ultraviolet absorber is an average molecular weight obtained by gel permeation chromatography (GPC) analysis in terms of standard polystyrene.
[0033] The above-mentioned ultraviolet absorbents of the present invention may be used alone or in combination of two or more kinds. In addition, other benzotriazole-based ultraviolet absorbents, hydroxyphenyltriazine-based ultraviolet absorbents, etc. may be used in combination as long as the effects of the present invention are not impaired.
[0034] In the hard coat film of the present invention, the hard coat layer contains the above-mentioned ultraviolet absorber of the present invention, so that the spectral characteristics (light transmittance at wavelengths of 365 nm, 405 nm and 436 nm) can satisfy the range of the present invention.
[0035] As described later, in the present invention, the thickness of the hard coat layer containing the ultraviolet absorber of the present invention is preferably more than 2.0 μm and less than 6.0 μm, and particularly preferably in the range of 3.0 μm to 5.0 μm. When the thickness of the hard coat layer is more than 2.0 μm and less than 6.0 μm, the blending amount of the ultraviolet absorber of the present invention is preferably in the range of 20 parts by mass to 60 parts by mass relative to 100 parts by mass of the ultraviolet curing resin of the hard coat layer. If the blending amount of the ultraviolet absorber of the present invention is less than 20 parts by mass, the thickness of the hard coat layer of the present invention is in the range of more than 2.0 μm and less than 6.0 μm, and the spectral characteristics of the present invention cannot be fully satisfied. On the other hand, if the blending amount of the ultraviolet absorber of the present invention exceeds 60 parts by mass, the ratio of the ultraviolet curing resin in the hard coat layer decreases, so that the adhesion of the hard coat layer to the film substrate may decrease, or the hardness of the hard coat layer may decrease, which is not suitable. When the thickness of the hard coat layer is in the range of 3.0 μm to 5.0 μm, the blending amount of the ultraviolet absorber of the present invention is preferably in the range of 30 parts by mass to 50 parts by mass per 100 parts by mass of the ultraviolet curing resin of the hard coat layer.
[0036] In addition, it is possible to further improve the surface hardness (scratch resistance) by incorporating inorganic oxide fine particles in the hard coat layer. In this case, the average particle diameter of the inorganic oxide fine particles is preferably in the range of 5 to 50 nm, more preferably in the range of 10 to 40 nm. If the average particle diameter is less than 5 nm, it is difficult to obtain sufficient surface hardness. On the other hand, if the average particle diameter exceeds 50 nm, the gloss and transparency of the hard coat layer are likely to decrease, and the flexibility may also decrease.
[0037] In the present invention, examples of the inorganic oxide fine particles include alumina, silica, etc. Among these, alumina, which is mainly composed of aluminum, is particularly suitable because it has high hardness and can be effective with a smaller amount than silica.
[0038] In the present invention, the content of inorganic oxide fine particles is preferably 0.1 to 10.0 parts by mass relative to 100 parts by mass of the ultraviolet curable resin of the hard coat layer. If the content of inorganic oxide fine particles is less than 0.1 parts by mass, it is difficult to obtain an effect of improving surface hardness (scratch resistance). On the other hand, if the content exceeds 10.0 parts by mass, the haze increases, which is not preferable.
[0039] The hard coat coating material for forming the hard coat layer may contain a photopolymerization initiator. As such a photopolymerization initiator, acetophenones such as IRGACURE 651 and IRGACURE 184 (both trade names: manufactured by BASF) and benzophenones such as IRGACURE 500 (trade name: manufactured by BASF) can be used.
[0040] A leveling agent can be used in the hard coat layer to improve the coating property, and known leveling agents such as fluorine-based, acrylic, siloxane-based, and their adducts or mixtures can be used. The blending amount can be in the range of 0.03 to 3.0 parts by mass per 100 parts by mass of the solid content of the resin of the hard coat layer. In addition, in touch panel applications, when adhesion using an optically transparent adhesive OCR is required for the purpose of adhesion to the cover glass (CG), transparent conductive member (TSP), liquid crystal module (LCM), etc. of the touch panel terminal, it is preferable to use an acrylic leveling agent or a fluorine-based leveling agent with high surface free energy (approximately 30 mN / m or more).
[0041] Other additives that may be added to the hard coat layer, if necessary, include an antifoaming agent, a surface tension adjusting agent, an antifouling agent, an antioxidant, an antistatic agent, a light stabilizer, etc., within the scope of not impairing the effects of the present invention.
[0042] The hard coat layer is formed by applying a hard coat coating material, which is prepared by dissolving or dispersing the ultraviolet absorbing agent of the present invention, a photopolymerization initiator, and other additives in a suitable solvent in addition to the ultraviolet curing resin, on the transparent substrate, drying, and then curing by irradiating with UV. The solvent can be appropriately selected according to the solubility of the resin to be blended, and may be any solvent that can uniformly dissolve or disperse at least the solid content (resin, ultraviolet absorbing agent, dye, photopolymerization initiator, other additives, etc.). Examples of such solvents include known organic solvents such as aromatic solvents such as toluene, xylene, and n-heptane, aliphatic solvents such as cyclohexane, methylcyclohexane, and ethylcyclohexane, ester solvents such as methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, and methyl lactate, ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, and alcohol solvents such as methanol, ethanol, isopropyl alcohol, and n-propyl alcohol, either alone or in combination.
[0043] The coating method of the hard coat paint forming the hard coat layer is not particularly limited, but after coating by a known coating method such as gravure coating, microgravure coating, fountain bar coating, slide die coating, slot die coating, screen printing, spray coating, etc., the coating is usually dried at a temperature of about 50 to 120°C.
[0044] The amount of ultraviolet (UV) irradiation after the formation of the hard coat layer may be any amount necessary to provide the hard coat layer with sufficient hardness, and can be appropriately set depending on the type of ultraviolet curing resin, etc.
[0045] In the present invention, the thickness (coating film thickness) of the hard coat layer is, for example, preferably more than 2.0 μm and less than 6.0 μm, and more preferably in the range of 3.0 μm to 5.0 μm. If the thickness of the hard coat layer is less than 2.0 μm, the necessary hardness (e.g., scratch resistance) is reduced, which is not preferable, whereas if the thickness of the hard coat layer is 6.0 μm or more, the hard coat layer is prone to curling, which reduces the handling properties during the manufacturing process, and is also not preferable from the viewpoint of thinning the hard coat film.
[0046] The hard coat film of the present invention is formed by laminating the above-mentioned hard coat layer on at least one side of a transparent substrate. For example, when a cycloolefin polymer film is used as the transparent substrate, it is also preferable to provide an easy-adhesion layer between the transparent substrate and the hard coat layer in order to improve the adhesion of the hard coat layer.
[0047] The resin used in the easy-adhesion layer is not particularly limited as long as it is a resin that forms a coating. For example, from the viewpoint of adhesion to the transparent substrate film (cycloolefin film), polyolefin resin, styrene acrylic resin, acrylic resin such as methyl methacrylate resin, epoxy resin, isocyanate resin, cellulose resin, or a mixture of two or more of these resins can be preferably used.
[0048] The coating thickness of the adhesion layer is not particularly limited, but is preferably in the range of 0.1 μm to 5.0 μm, which is within a range that does not adversely affect the adhesion to the base film and the hard coat layer, or the pencil hardness of the hard coat layer.
[0049] As described above, the hard coat film of the present invention comprises a transparent substrate and a hard coat layer formed on at least one surface thereof and made of an ultraviolet curable resin containing a sesamol-type benzotriazole ultraviolet absorber having a weight average molecular weight in the range of 15,000 to 35,000.
[0050] The hard coat film of the present invention is further characterized by satisfying the following spectral characteristics. That is, the hard coat film of the present invention is characterized by a light transmittance at a wavelength of 365 nm of less than 1%, a light transmittance at a wavelength of 405 nm of less than 10%, and a light transmittance at a wavelength of 436 nm of 81% or more. The specific method for measuring the light transmittance at each of the above wavelengths will be described later in the description of the examples.
[0051] The hard coat film of the present invention has a hard coat layer made of an ultraviolet curable resin containing the ultraviolet absorber of the present invention, and the above-mentioned spectral characteristics (light transmittance at each wavelength of 365 nm, 405 nm, and 436 nm) satisfy the range of the present invention, so that the light transmittance at wavelengths represented by 365 nm and 405 nm, which cause damage such as deterioration of some polymers used in organic EL displays and fading and discoloration of dyes, can be suppressed to less than 10%, and damage such as deterioration of some polymers and fading and discoloration of dyes can be suppressed. Furthermore, in order to improve the durability (light resistance) of the light emitting element of recent organic EL displays, it is required to sufficiently reduce the light transmittance at 405 nm to protect the light emitting element, and the hard coat film of the present invention can suppress the light transmittance at a wavelength of 405 nm to less than 10%, and can improve the durability (light resistance) of the light emitting element of recent organic EL displays. In addition, while the wavelength of 436 nm in the visible light region is required to have as high a light transmittance as possible to ensure the brightness of the display of an organic EL display, the hard coat film of the present invention makes it possible to obtain a light transmittance of 81% or more for the wavelength of 436 nm in the visible light region, and does not adversely affect the brightness of the display of an organic EL display.
[0052] The hard coat film of the present invention is further characterized in that after the hard coat film is subjected to an accelerated light resistance test in accordance with JIS-K-5600-7-7 for 100 hours, the light transmittance at a wavelength of 365 nm is less than 1%, the light transmittance at a wavelength of 405 nm is less than 10%, and the light transmittance at a wavelength of 436 nm is 81% or more. The above light resistance test will be described in more detail in the Examples section below.
[0053] For the purpose, the light transmittance of each of the above-mentioned wavelengths must maintain its performance even after a light fastness test at wavelengths of 365 nm and 405 nm, which cause damage such as deterioration of some polymers and fading or discoloration of dyes, and at a wavelength of 405 nm, which contributes to protecting the light emitting element of recent organic EL displays. The hard coat film of the present invention can suppress the increase in light transmittance at wavelengths of 365 nm and 405 nm even after a light fastness test by providing a hard coat layer made of an ultraviolet curable resin containing the ultraviolet absorber of the present invention, and can suppress the deterioration of the display of the organic EL display. In addition, the hard coat film of the present invention can also suppress the increase in light transmittance at a wavelength of 436 nm in the visible light region even after a light fastness test, and can maintain the brightness of the display of the organic EL display.
[0054] As described above in detail, according to the present invention, when used as a protective film for the surface of an organic EL display, it is possible to obtain a hard coat film that can improve the durability (light resistance) of the light emitting element of the organic EL display without adversely affecting the color and brightness of the display of the organic EL display, and can suppress deterioration of the display of the organic EL display. Furthermore, according to the present invention, it is possible to obtain a hard coat film that can maintain the above-mentioned performance even after the hard coat film is subjected to a light resistance test. Furthermore, according to the present invention, it is possible to obtain a hard coat film that allows the film to be made thin. EXAMPLES
[0055] Next, the embodiment of the present invention will be described more specifically with reference to examples, but the present invention is not limited to the following examples. In the following description, "parts" means parts by mass unless otherwise specified, and "%" means % by mass unless otherwise specified.
[0056] Example 1 [Preparation of Coating Solution for Forming Hard Coat Layer] The present invention is based on 94 parts of an acrylate-based ultraviolet curing resin coating material containing a sesamol-type benzotriazole-based ultraviolet absorber (HFC-UVA-13 (trade name); manufactured by Harima Chemicals Co., Ltd.; weight average molecular weight of sesamol-type benzotriazole-based ultraviolet absorber: 22000), and 5 parts of Irgacure 184 (photopolymerization initiator, manufactured by BASF) and 1 part of a surface modifier (Ftergent 681; manufactured by Neos Co., Ltd.) are mixed together, and diluted with toluene / propylene glycol monomethyl ether acetate = 15 / 85 (parts by weight) to prepare a coating liquid for forming a hard coat layer (hereinafter also referred to as "hard coat coating material") with a final solid content concentration of 30%.
[0057] [Preparation of hard coat film] The above hard coat paint was applied to one side of a 25 μm-thick triacetyl cellulose film, TJ25UL (manufactured by Fujifilm Corporation), using a bar coater, and then dried with hot air in a drying oven at 80°C for 1 minute to form a coating layer with a coating thickness of 3.0 μm. This was then irradiated with a UV irradiation device set at a height of 60 mm from the coated surface, with a UV irradiation dose of 100 mJ / cm. 2 The coating was cured by irradiation with ultraviolet light of 100 .ANG. to prepare a hard coat film of this Example 1.
[0058] Example 2 A hard coat film of Example 2 was produced in the same manner as in Example 1, using a hard coat coating material prepared in the same manner as in Example 1, except that an acrylate-based ultraviolet curable resin coating material containing the sesamol-type benzotriazole-based ultraviolet absorber of the present invention (HFC-UVA-13 (product name); manufactured by Harima Chemicals Co., Ltd.; weight average molecular weight of sesamol-type benzotriazole-based ultraviolet absorber: 27,000) was used as the acrylate-based ultraviolet curable resin coating material.
[0059] Example 3 A hard coat film of Example 3 was produced in the same manner as in Example 1, using a hard coat coating material prepared in the same manner as in Example 1, except that an acrylate-based ultraviolet curable resin coating material containing the sesamol-type benzotriazole-based ultraviolet absorber of the present invention (HFC-UVA-13 (product name); manufactured by Harima Chemicals Co., Ltd.; weight average molecular weight of sesamol-type benzotriazole-based ultraviolet absorber: 35,000) was used as the acrylate-based ultraviolet curable resin coating material.
[0060] Example 4 A hard coat film of Example 4 was produced in the same manner as in Example 1, using a hard coat coating material prepared in the same manner as in Example 1, except that an acrylate-based ultraviolet curable resin coating material containing the sesamol-type benzotriazole-based ultraviolet absorber of the present invention (HFC-UVA-13 (trade name); manufactured by Harima Chemicals Co., Ltd.; weight average molecular weight of sesamol-type benzotriazole-based ultraviolet absorber: 15,000) was used as the acrylate-based ultraviolet curable resin coating material.
[0061] Example 5 The hard coat film of Example 5 was produced in the same manner as in Example 1, except that the hard coat coating material of Example 1 was used and the substrate was changed to a polyethylene terephthalate film A4360 (manufactured by Toyobo Co., Ltd.) having a thickness of 50 μm.
[0062] Example 6 The hard coat film of Example 6 was produced in the same manner as in Example 1, except that the hard coat coating material of Example 1 was used and the substrate was changed to a cycloolefin polymer film having a thickness of 13 μm, Zeonoafilm ZF12 (manufactured by Zeon Corporation).
[0063] Example 7 The hard coat film of Example 7 was produced in the same manner as in Example 1, except that the hard coat coating material of Example 1 was used and the substrate was changed to a cycloolefin polymer film having a thickness of 22 μm, Zeonoafilm ZD12 (manufactured by Zeon Corporation).
[0064] Example 8 The hard coat film of Example 8 was produced in the same manner as in Example 1, except that the hard coat coating material of Example 1 was used and the substrate was changed to a cycloolefin polymer film having a thickness of 26 μm, Zeonoafilm ZD12 (manufactured by Zeon Corporation).
[0065] Example 9 A hard coat film of Example 9 was produced in the same manner as in Example 8, except that the coating thickness of the coating layer in Example 8 was changed to 5.0 μm.
[0066] Comparative Example 1 [Preparation of hard coat paint] A hard coat paint with a final solids concentration of 30% was prepared by blending 94 parts of an acrylate-based ultraviolet curing resin paint containing a sesamol-type benzotriazole-based ultraviolet absorber (HFC-UVA-13 (trade name); manufactured by Harima Chemicals Co., Ltd.; weight average molecular weight of sesamol-type benzotriazole-based ultraviolet absorber: 13,000) as the base material, 5 parts of Irgacure 184 (photopolymerization initiator; manufactured by BASF) and 1 part of a surface modifier (Ftergent 681; manufactured by Neos Co., Ltd.). The resulting mixture was diluted with toluene / propylene glycol monomethyl ether acetate = 15 / 85 (parts by weight) to prepare a hard coat paint with a final solids concentration of 30%. [Preparation of hard coat film] A hard coat film of Comparative Example 1 was produced in the same manner as in Example 1, except that the coating material for hard coat having the above composition was used.
[0067] Comparative Example 2 A hard coat film of Comparative Example 2 was produced in the same manner as in Comparative Example 1, except that the coating thickness of the coating layer in Comparative Example 1 was changed to 5.0 μm.
[0068] Comparative Example 3 A hard coat film of Comparative Example 3 was produced in the same manner as in Comparative Example 1, using a hard coat paint prepared in the same manner as in Comparative Example 1, except that an acrylate-based ultraviolet curing resin paint containing a sesamol-type benzotriazole-based ultraviolet absorber (HFC-UVA-13 (product name); manufactured by Harima Chemical Co., Ltd.; weight average molecular weight of sesamol-type benzotriazole-based ultraviolet absorber: 37,000) was used as the acrylate-based ultraviolet curing resin paint.
[0069] Comparative Example 4 A hard coat film of Comparative Example 4 was produced in the same manner as in Comparative Example 3, except that the coating thickness of the coating layer in Comparative Example 3 was changed to 5.0 μm.
[0070] Comparative Example 5 [Preparation of hard coat paint] A hard coat paint with a final solids concentration of 30% was prepared by mixing 84 parts of an acrylate-based ultraviolet curing resin (NK Ester A-9550 (trade name); manufactured by Shin-Nakamura Chemical Co., Ltd.) as the base, 10 parts of a benzotriazole-based ultraviolet absorber (Adeka STAB LA-36 (trade name); manufactured by ADEKA Corporation), 5 parts of Irgacure 184 (photopolymerization initiator, manufactured by BASF), and 1 part of a surface modifier (Ftergent 681; manufactured by NEOS Corporation). The mixture was diluted with toluene / propylene glycol monomethyl ether acetate = 15 / 85 (parts by weight) to prepare a hard coat paint with a final solids concentration of 30%. [Preparation of hard coat film] A hard coat film of Comparative Example 5 was produced in the same manner as in Example 1, except that the coating material for hard coat having the above composition was used.
[0071] Comparative Example 6 [Preparation of hard coat paint] A hard coat paint with a final solids concentration of 30% was prepared by mixing 90 parts of an acrylate ultraviolet curing resin (NK Ester A-9550 (trade name); manufactured by Shin-Nakamura Chemical Co., Ltd.) as the base, 4 parts of a cyanine dye (NK-9994 (trade name); manufactured by Hayashibara Co., Ltd.), 5 parts of Irgacure 184 (photopolymerization initiator, manufactured by BASF), and 1 part of a surface modifier (Ftergent 681; manufactured by Neos Co., Ltd.), and diluting with toluene / propylene glycol monomethyl ether acetate = 15 / 85 (parts by weight). [Preparation of hard coat film] A hard coat film of Comparative Example 6 was produced in the same manner as in Example 1, except that the coating material for hard coat having the above composition was used.
[0072] <Evaluation> The hard coat films of the Examples and Comparative Examples prepared as described above were evaluated for the following items. The results are summarized in Table 1.
[0073] <Coating thickness> The thickness of the coating of the hard coat layer (HC layer) was measured using a Thin-Film Analyzer F20 (product name) (manufactured by FILMETRICS).
[0074] <Light transmittance at each wavelength> The light transmittance of the hard coat film at each wavelength (365 nm, 405 nm, 436 nm) was measured using a spectrophotometer U-3310 manufactured by Hitachi High-Technologies Corp. The measurement was performed in the wavelength range of 250 to 800 nm at a scan speed of 600 nm / min.
[0075] <Light resistance test> Each of the hard coat films produced in the Examples and Comparative Examples was subjected to an accelerated light resistance test using a Xenon Weather Ometer (conforming to JIS-K-5600-7-7 under the following conditions). Light source: Xenon arc Temperature: 63℃ Relative humidity: 50% Irradiance: 50W / m 2 Radiation time: 100 hours Rainfall period and time: Not set
[0076] The light transmittance at each wavelength of the hard coat film after the light resistance test was measured in the same manner as above.
[0077] [Table 1]
[0078] As is clear from the results of Table 1 above, the hard coat film of the present invention has a hard coat layer made of an ultraviolet curable resin containing the ultraviolet absorber of the present invention, and the above-mentioned spectral characteristics (light transmittance at each wavelength of 365 nm, 405 nm, and 436 nm) satisfy the range of the present invention, so that the light transmittance at wavelengths represented by 365 nm and 405 nm, which cause damage such as deterioration of some polymers used in organic EL displays and fading and discoloration of dyes, can be suppressed to less than 10%, and damage such as deterioration of some polymers and fading and discoloration of dyes can be suppressed. Furthermore, in order to improve the durability (light resistance) of the light emitting element of recent organic EL displays, it is required to sufficiently reduce the light transmittance at 405 nm to protect the light emitting element, but the hard coat film of the present invention can suppress the light transmittance at a wavelength of 405 nm to less than 10%, and can improve the durability (light resistance) of the light emitting element of recent organic EL displays. In addition, the wavelength of 436 nm in the visible light region is required to have as high a light transmittance as possible to ensure the brightness of the display of an organic EL display. However, the hard coat film of the present invention makes it possible to obtain a light transmittance of 81% or more for the wavelength of 436 nm in the visible light region, and does not adversely affect the brightness of the display of an organic EL display.
[0079] Furthermore, for the purpose, the light transmittance of each of the above-mentioned wavelengths must maintain its performance even after the light fastness test at wavelengths of 365 nm and 405 nm, which cause damage such as deterioration of some polymers and fading and discoloration of dyes, and at wavelength of 405 nm, which contributes to protecting the light emitting element of recent organic EL displays. However, the hard coat film of the present invention has a hard coat layer made of an ultraviolet curable resin containing the sesamol-type benzotriazole-based ultraviolet absorber of the present invention, so that the increase in the light transmittance at wavelengths of 365 nm and 405 nm can be suppressed even after the light fastness test, and the deterioration of the display of the organic EL display can be suppressed. In addition, the hard coat film of the present invention can also suppress the increase in the light transmittance at the wavelength of 436 nm in the visible light region even after the light fastness test, and can maintain the brightness of the display of the organic EL display.
[0080] In contrast, the hard coat film of Comparative Example 1, which is provided with a hard coat layer made of an ultraviolet curable resin containing a sesamol-type benzotriazole-based ultraviolet absorber having a weight-average molecular weight of less than 15,000, cannot sufficiently reduce the light transmittance at 405 nm, and therefore the display of the organic EL display is deteriorated. Furthermore, in the hard coat film of Comparative Example 2, although the light transmittance at 405 nm can be reduced by adjusting (thickening) the film thickness of the hard coat layer of Comparative Example 1, the performance cannot be maintained even after a light resistance test at a wavelength of 405 nm, and there are problems in that the display of the organic EL display is deteriorated and that the durability (light resistance) of the light emitting element cannot be improved. It should be noted that a method of further thickening the film thickness of the hard coat layer (for example, 6.0 μm or more) and maintaining the performance even after a light resistance test at a wavelength of 405 nm is conceivable, but thickening the hard coat layer is not preferable because it goes against the technical trend of curling the hard coat film, cracking the hard coat layer, and thinning the hard coat film.
[0081] In addition, the hard coat film of Comparative Example 3, which is provided with a hard coat layer made of an ultraviolet curable resin containing a sesamol-type benzotriazole-based ultraviolet absorber having a weight-average molecular weight of more than 35,000, cannot maintain its performance even after a light resistance test at a wavelength of 405 nm, and there are problems in that the display of the organic EL display deteriorates and that the durability (light resistance) of the light-emitting element cannot be improved. Furthermore, in the hard coat film of Comparative Example 4, although the performance can be maintained even after a light resistance test at a wavelength of 405 nm by adjusting (thickening) the film thickness of the hard coat layer of Comparative Example 3, the performance cannot be maintained after a light resistance test at a wavelength of 436 nm, and there is a problem in that the brightness of the display of the organic EL display cannot be sufficiently secured. It should be noted that a method of further thickening the film thickness of the hard coat layer (for example, 6.0 μm or more) and maintaining its performance even after a light resistance test at a wavelength of 436 nm is conceivable, but thickening the hard coat layer is not preferable because it goes against the technical trend of curling of the hard coat film, cracking of the hard coat layer, and thinning of the hard coat film.
[0082] Furthermore, in the hard coat film of Comparative Example 5 using an ultraviolet absorber other than the ultraviolet absorber of the present invention, the light transmittance at a wavelength of 405 nm cannot be sufficiently reduced, so there is a problem that protection of the organic EL display cannot be achieved. Also, in the hard coat film of Comparative Example 6 not using the ultraviolet absorber of the present invention, although there is no problem with the initial light transmittance at each wavelength, the change in light transmittance at each wavelength after the light resistance test is extremely large, so there is a problem that improvement in durability (light resistance) of the light emitting element of the organic EL display cannot be achieved.
Claims
1. A hard coat film comprising a transparent substrate and a hard coat layer formed of an ultraviolet curable resin containing a sesamol-type benzotriazole-based ultraviolet absorber having a weight average molecular weight in the range of 15,000 to 35,000 laminated on at least one surface thereof, the hard coat film having a light transmittance of 0.1% or less at a wavelength of 365 nm, a light transmittance of less than 10% at a wavelength of 405 nm, and a light transmittance of 81% or more at a wavelength of 436 nm.
2. The hard coat film according to claim 1, characterized in that after the hard coat film is subjected to an accelerated light resistance test in accordance with JIS-K-5600-7-7 for 100 hours, the light transmittance at a wavelength of 365 nm is 0.1% or less, the light transmittance at a wavelength of 405 nm is less than 10%, and the light transmittance at a wavelength of 436 nm is 81% or more.
3. 3. The hard coat film according to claim 1, wherein the thickness of the hard coat layer is more than 2.0 μm and less than 6.0 μm.
4. 3. The hard coat film according to claim 1, wherein the amount of the sesamol-type benzotriazole-based ultraviolet absorber is 20 to 60 parts by mass per 100 parts by mass of the ultraviolet curable resin of the hard coat layer.
5. 3. The hard coat film according to claim 1, wherein the transparent substrate is a triacetyl cellulose film, a polyethylene terephthalate film, or a cycloolefin polymer film.
Citation Information
Patent Citations
Benzotriazole derivative compound
JP2012025680A
Protective layer transfer sheet, combination of thermal transfer sheet and protective layer transfer sheet, printed material, and method of forming printed material
JP2013180455A
Benzotriazole (CO)polymer, ultraviolet absorbing coating material containing the same, and film coated with the coating material
JP2018177976A
Optical laminate, image display device, and touch panel sensor
JP2020154316A
Triazine ring-containing polymer and composition for film formation comprising same
WO2013094664A1